1999
DOI: 10.1094/phyto.1999.89.2.118
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Change in Viral Genome-Associated Protein of Potato Virus Y Correlates with Resistance Breaking in ‘Virgin A Mutant’ Tobacco

Abstract: Tobacco cultivar Virgin A Mutant (VAM) is reported to have the recessive potyvirus resistance gene va. Varied levels of resistance were observed in VAM plants inoculated with Japanese potato virus Y (PVY) isolates. VAM was highly resistant to most of the PVY isolates tested and tolerant to three necrotic strain isolates of PVY-T. Based on data obtained from tissue printing and press blotting, the resistance appeared to be mainly at the level of cell-to-cell movement. PVY replicated in VAM proto-plasts, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Similar cross-infectivity effects are also expected between tobacco (Nicotiana tabacum) and pepper resistance genes. Indeed, it was shown previously that the VPg of PVY was also the pathogenicity factor corresponding to the va gene in tobacco (40,41). Sequence comparisons indicated that the S101G and D119G substitutions in the VPg of PVY SON41p allowed the breakdown of the va 2 resistance allele in tobacco.…”
Section: Discussionmentioning
confidence: 93%
“…Similar cross-infectivity effects are also expected between tobacco (Nicotiana tabacum) and pepper resistance genes. Indeed, it was shown previously that the VPg of PVY was also the pathogenicity factor corresponding to the va gene in tobacco (40,41). Sequence comparisons indicated that the S101G and D119G substitutions in the VPg of PVY SON41p allowed the breakdown of the va 2 resistance allele in tobacco.…”
Section: Discussionmentioning
confidence: 93%
“…Such an alternative adaptation process has been described for the acquisition of virulence for other plant viruses such as Rice yellow mottle sobemovirus and Beet necrotic yellow vein furovirus in the presence of Rymv1-2 (in rice genotypes) and Rz1 (in beet genotypes) resistance genes, respectively (Pinel-Galzi et al 2007;Acosta-Leal et al 2010). The central part of the VPg has already been associated to a va resistance breaking phenotype for Tobacco vein mottling potyvirus (Nicolas et al 1997) and PVY (Masuta et al 1999), but amino acids substitutions observed under our experimental conditions did not correspond to those previously proposed (i.e. K/E 105 or R/E 105 ) as genetic determinants for overcoming the PVY-resistance gene va.…”
Section: Q E R F E V R R K M V E D D E I E T Q a L S H T S I Hmentioning
confidence: 98%
“…Plants were scored for symptoms, and viral concentrations were determined either by ELISA or by RNA gel blot analysis. Tissue prints were prepared as essentially described by Masuta et al (1999). Immature G. max seeds were cut in half and pressed onto a nitrocellulose membrane.…”
Section: Viral Inoculation and Detectionmentioning
confidence: 99%